Pine needles as urban atmospheric pollution indicators: Heavy metal concentrations and Pb isotopic source identification. (June 2022) - Chen, Yizhu; Ning, Yongqiang; Bi, Xiangyang; Liu, Jinling; Yang, Shaochen; Liu, Zhifu; Huang, Wenmin
Abstract: Pine needles are reliable passive bio-samplers that can be used to monitor atmospheric pollution levels. This study applied Pb isotope and multivariate statistical analyses to pine needles to examine the characteristics, sources, and ecological risks of atmospheric heavy metal pollution in the cities of the middle reaches of the Yangtze River, China. The heavy metal concentrations were higher than those measured in pine needles elsewhere in the world. They were higher in the metropolitan city (Wuhan) than in the medium-sized city (Yichang) and lowest in the natural setting (Shennongjia Forestry District), which is consistent with trends in urbanization and industrialization. Principal component analysis grouped the metals into three main sets associated with industrial activities and traffic sources. The Pb composition determined the main anthropogenic Pb sources were vehicle exhaust and industrial activities related to the lead-zinc ore, only a few of which were coal combustion. Three risk assessment indexes (pollution load index, ecological risk index, and bioconcentration factor) suggest that atmospheric heavy metals in the study area pose moderate environmental and health risks. Graphical abstract: Image 1 Highlights: Pine needles are a useful tool for monitoring atmospheric heavy metals in cities. Pb isotope in pine needles can determine anthropogenic and natural sources. The main anthropogenic Pb sources varied in different cities. The main heavy metal sources were industry, traffic, and domestic waste.